Effects of the multidomain intervention with nutritional supplements on cognition and gut microbiome in early symptomatic Alzheimer’s disease: a randomized controlled trial - Lee, Eun Hye; Kim, Geon Ha; Park, Hee Kyung; Kang, Hae Jin; Park, Yoo Kyoung; Lee, Hye Ah; Hong, Chang Hyung; Moon, So Young; Kang, Woorim; Oh, Hyun-Seok; Yoon, Hai-Jeon; Choi, Seong Hye; et al. (Frontiers in Aging Neuroscience, 2023)
The SoUth Korean study to PrEvent cognitive impaiRment and protect BRAIN health through lifestyle intervention in at-risk elderly people (SUPERBRAIN) is a part of the World-Wide Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability (WW-FINGERS) network. This study aimed to demonstrate the effects of the SUPERBRAIN-based multidomain intervention with nutritional supplements in amyloid positive emission tomography (PET) proven early symptomatic Alzheimer's disease patients.Methods: Forty-six participants who were diagnosed with mild cognitive impairment or mild dementia and were positive in the amyloid PET study randomized into three groups: group A, the multidomain intervention with nutritional supplements; group B, nutritional supplements only; and a control group. The primary outcome was a change in the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) total scale index score after an 8-week intervention. Secondary outcomes, including gut microbiome data, were also analyzed.The RBANS total scale index score improved significantly in group A compared with group B (p < 0.032) and compared with the control group (p < 0.001). After intervention, beta diversity of the gut microbiome between group A and the control group increased, and patients in group A were more enriched with Bifidobacterium.SUPERBRAIN-based multidomain intervention with nutritional supplements improves cognition and gut microbiota in patients with early symptomatic Alzheimer's disease who were amyloid-positive by PET.